Effects of Three Extraction Methods on Recovery, Quality, Storage Stability and Frying Characteristics of Coconut Oil - Suhardiyono, (1992)
Three improved methods for coconut oil extraction us ingacetic acid a baker's yeast, and mixed enzymes with respect to oil recovery, quality,storage stability,and frying characteristics were investigated. In the initial process , cream was separated from the coconut milk. Treatment of the cream with 0.1-0.4% acetic acid or 0.5-2g baker's yeast for 10-14 hrs resulted in further separation of the cream into two phases;the upper phase containing oil-rich fraction and the lower phase consisting of aqueously fraction. The oil phase was finally boiled for 20 minutes to remove moisture. The other extraction method was based on the combined action of cellulase, amylase, protease, and polygalacturonas eat 0.1 to 1% on grated coconut meat at pH 4 to 8, 40°to 60°C for 30 minutes and centrifugation at 10,000rpm.